Valores e educação : a escola deve educar para valores? - Paim, Viviane Catarini (My University, 2014)
The present dissertation has as main theme the question of values in relation to the educational process at school. Its main objective is to analyze the task of school on the education for values, compared to the social and cultural changes and their implications in the educational process. To carry out this purpose, the method of approach is the analytical-interpretative, and the dissertation work is divided into three chapters. The first chapter will describe the contemporary society and its major transformations on social and culture scope. Therefore, it will use the contributions of the sociologist Zygmunt Bauman, in order to show the main features present in the social context, so that then we can understand the role of schools entered in this context. After presenting this background, the second chapter, the dissertative work has the objective to highlight the issue of values and, to do this, rely on the theoretical philosopher Max Scheler, presenting his central ideas about this theory of values. From the description of society referenced by Bauman and value theory, formulated by Scheler, the third chapter has the objective to situate and analyze the school’s mission face social and cultural transformations and their educational process, in particular, compared to values. And for understanding the school’s mission in today’s context we will analyze the Political Pedagogical Project of the Jardim América State Elementary School, on the city of Vacaria, in Rio Grande do Sul, because through the analysis of this document it is possible to understand and evaluate the desired targets with the pedagogical actions of the school, and also see how the institution sees the formation of human beings, and if, to do it, the school takes care to educate for values. In light of this analysis, finally, we will list some values that are essential, in order to weave a relationship between school, society and values and understand that schools must educate for values.
A presente dissertação traz como tema principal a questão dos valores em relação ao processo educativo escolar. Seu principal objetivo é analisar a tarefa da escola quanto à educação para valores, frente às transformações sociais e culturais e suas implicações no processo educativo. Para a realização de tal propósito, o método de abordagem será o analítico-interpretativo, sendo que o trabalho dissertativo está dividido em três capítulos. O primeiro capítulo descreverá a sociedade contemporânea e suas principais transformações no âmbito social e cultural. Por isso, se valerá das contribuições do sociólogo Zygmunt Bauman, no intuito de apresentar as principais características presentes no contexto social, para que, em seguida, se possa compreender o papel da escola inserida nesse contexto. Após a apresentação desse panorama, no segundo capítulo, o trabalho dissertativo terá o intuito de destacar o tema dos valores e, para isso, contará com o aporte teórico do filósofo Max Scheler, apresentando suas ideias centrais acerca de sua teoria dos valores. A partir da descrição da sociedade referenciada por Bauman e da teoria dos valores, formulada por Scheler, no terceiro capítulo, o objetivo será situar e analisar a missão da escola diante das transformações sociais e culturais e seu processo educativo, em especial, frente aos valores. E para a compreensão da missão da escola no contexto hodierno far-se-á a análise do Projeto Político-Pedagógico da Escola Estadual de Ensino Fundamental Jardim América do município de Vacaria, no Rio Grande do Sul, porque, através da análise desse documento, é possível compreender e avaliar as metas pretendidas com as ações pedagógicas da Escola, e, além disso, constatar como a respectiva instituição concebe a formação do ser humano, e se, para realizá-la, ela tem a preocupação de educar para valores. À luz dessa análise, por fim, elencar-se-ão alguns valores imprescindíveis, a fim de poder tecer uma relação entre escola, sociedade e valores e compreender que a instituição escolar deve educar para valores.
Keywords: Valores - Educação; Values - Education